Analisis Pengendalian Banjir pada Wilayah Kelurahan Takkalasi Kabupaten Barru - Ishak, Wanda Mey Fasthika; Yusuf, Andi Rumpang; Cangara, Satriawati (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Flooding is the most frequent natural disaster in Indonesia. It is defined as a condition in which a region is submerged by a large volume of water due to high rainfall. Takkalasi Village, through which the Takkalasi River flows, is considered a flood-prone area. Given the recurring floods, a comprehensive study is needed to find solutions. This research was conducted in Barru Regency, specifically in the Takkalasi River, aiming to analyze rainfall intensity and flood discharge for 25, 50, and 100-year return periods, as well as flood control methods. The planned flood discharge was analyzed using the Nakayasu Synthetic Unit Hydrograph (HSS) method, yielding 25-year (Q25) discharge at 77.22 m³/s, 50-year (Q50) at 78.64 m³/s, and 100-year (Q100) at 79.97 m³/s. Analysis showed river overflow at 67.888 m³/s, indicating that when both high tides and continuous rainfall for up to 7 hours occur, flooding affects the Takkalasi area. To mitigate this, the construction of two water gates along the Takkalasi River is necessary to prevent overflow during such events.